Montagem ucrônica: uma abordagem para o agenciamento entre Arte e Tecnologia nas artes audiovisuais - Leonardo da Silva Souza (2014)
This work adresses the way of agency between Art and technology. From the question of Pimentel (2011) on how digital technology can widen specific knowledge of the artistic field, this work found in the conceptual axis of Couchot (1999) the proposal that, for the purposes of that question, artistic and technological models should be transcended. Driven by artistic practice, the presented work proposes that in Deleuze (2005) and Guattari (2008; 2011) the notion of deterritorialization should be dealt as a form of transcendence of models. To ensure adequate treatment of deterritorialization as a form of transcendence, correlations between computational model and artistic territory, agency and technological autonomy are described, characterizing the creation dialog with technologies that propose sense in artistic creation, called here rizomorfic technologies. Based on these correlations, the deterritorializations of time, image, subject and audiovisual work from the agency with rizomórfica technology have been observed. Thus, it was possible to demonstrate that the notion of time stands for the articulating point of image, subject and artwork notions widening, through its deterritorialization, the notions of mountage and composition in audiovisual art, thus, enabling the construction of the notion called uchronic montage.